The nurses who work in intensive care units: Profile and Professional Training - Silvia Henriques Camelo (Universidad de Alicante, 2015)
Objective: To identify the profile of the professional nurse working in ICU. Methodology: It is an integrative review and data collection was performed in four electronic databases from January to June 2012. We selected 21 articles, published from 2008 to 2011. We identified two categories related to nurse profile: Social Profile and academic background of the ICU nurses and nurse's training to work in intensive care units. Results: The results showed female nurses, young, formed of time ranging from one to 25 years. Identifies the need for professional development with technical and scientific update through training, specialization and graduate. Conclusion: The study should elicit reflection of nurses and managers of health services as the appropriate profile for the development activities in highly complex units.